THE IMPACT OF INFLUENCERS ON CONSUMER BUYING INTEREST: (TIKTOK LIVE SHOP RAFFINAGITA) - Devy Widya Apriandi; Bismantara Bismantara; Ni Made Vinolita Wijayanti (STIESA Press, 2022)
Social media is a platform that connects people especially between business organizations and customers. Social media is an online media, where users can easily participate, share, and create content including blogs, social networks, wikis, forums and virtual worlds in their applications. The increase in social media users in Indonesia, both websites, blogs, and applications, has developed quite rapidly and is high. The following graph data obtained. The research method used is descriptive verification method with a quantitative approach. The object of research examined in this study examines the the influence of influencers on consumer buying interest on tiktok live shop. The unit of analysis is Raffi Nagita's Tiktok Live Shop. This research was conducted with a research design designed to obtain an overview of the influencer's influence on consumers' buying interest in Tiktok live shop. Based on the results of the study, it is known that the influence of influencer (X) on Raffi Nagita's Tiktok Shop Live account is considered very good with the indicator interval value of the questionnaire on influencers categorized as very good, the highest total score is 322 while the lowest score is 292. Based on the results of the research on the variable of consumer buying interest (Y) on Tiktok Shpo Raffi Nagita with the indicator value of the questionnaire interval on consumer buying interest in the good category based on consumer buying interest Tiktok Shop Raffi Nagita got the highest score of 308 and the lowest was 264. So influencers have an influence on consumer buying interest at Raffi Nagita's Tiktok Shop.